Knowledge and Compliance of Standard Precautions among Student Nurses - Labrague, Leodoro Jabien; Rosales, Rheajane Aguilar; Tizon, Maricel Mabulac (International Journal of Advanced Nursing Studies, 2012)
Student nurses are often exposed to various infections during their clinical exposure. Knowledge and compliance with standard precautions is essential in the prevention of health care infections and protection of patients as well as medical workers from exposure to infectious agents. This investigation assessed the knowledge and degree of compliance regarding standard precautions among student nurses in a government university in Samar, Philippines. A cross-sectional study was adopted for this investigation and data were collected over a period of one month from April 8 to May 7, 2012. Fifty eight student nurses who were enrolled in the university were all asked to complete the self report questionnaires regarding standard precautions. Vast majority (89.65%) of the student nurses have good knowledge (m = 14.45/19) and high compliance (m = 3.59) of standard precautions. The use of mask has the highest degree of compliance (m = 3.95) while the use of eye goggles has the lowest degree of compliance (m = 3.19). Findings suggest no significant association between knowledge and compliance with standard precautions. Teaching approaches must be geared towards intensifying further the compliances especially with the use of other protective equipments such eye goggles and gloves. Furthermore, environment that models and promotes standard precaution practices should be developed by the faculty.